Exploring the experiences of teenagers with cochlear implants. (1st November 2016) - Watson, Victoria; Verschuur, Carl; Lathlean, Judith
Abstract : Objectives : Teenage cochlear implant users' perceptions of deafness, surgery, fitting of the device and life as a cochlear implant wearer were explored in order to gain a more comprehensive understanding of teenagers' experiences of living with the device. Methods : Semi-structured in-depth interviews were undertaken and analysed using thematic analysis. Ten teenagers aged 14–16 years with at least one cochlear implant were interviewed. Results : Seven teenagers experienced great pre-operative anxiety and two reported significant post-operative pain. Four of the teenagers described a mismatch between their expectations and the disappointing reality of adjusting to the device. However, all the teenagers reported an enhanced sense of well-being as a result of being able to interact more easily with their world around them. The teenagers differed in the extent to which they identified with the hearing and deaf world. Discussion : Despite the early challenges, over time the teenagers experienced many functional and psychosocial benefits. Most felt their lives were now easier as a result of the cochlear implant(s). They described complex, flexible identities. Conclusions : By giving prominence to the teenagers' voices this study has added new knowledge concerning their experience of surgery. The findings also more fully revealed the challenges of adjusting to the device and the impact of having a cochlear implant on the teenagers' identities. Clinical recommendations are made to address the gaps in service highlighted by these findings.